Heterozygous Alterations of TNFRSF13B/TACI in Tonsillar Hypertrophy and Sarcoidosis. (15th July 2013) - Speletas, Matthaios; Salzer, Ulrich; Florou, Zoe; Petinaki, Efthimia; Daniil, Zoe; Bardaka, Fotini; Gourgoulianis, Konstantinos I.; Skoulakis, Charalampos; Germenis, Anastasios E.
Abstract : TNFRSF13B/TACI defects have been associated with CVID pathogenesis and/or phenotype, especially the development of benign lymphoproliferation and autoimmunity. Our purpose was to investigate the role of TNFRSF13B/TACI defects in the pathogenesis of two common lymphoproliferative disorders, namely, sarcoidosis and tonsillar hypertrophy (TH). 105 patients (71 with sarcoidosis and 34 with TH, including 19 without infectious causative and 15 due to Haemophilus influenzae ) were analyzed for TNFRSF13B/TACI defects. Two out of 19 TH patients without infectious cause (10.5%) and 2 patients with sarcoidosis (2.8%) displayed rare TNFRSF13B/TACI defects (I87N, L69TfsX12, E36L, and R202H, resp.). Both mutations identified in TH patients have been assessed as deleterious for protein function, while the patient with the R202H mutation and sarcoidosis exhibited also sIgG4D. Our study further supports the notion that TNFRSF13B/TACI defects alone do not result in CVID but may be also found frequently in distinct clinical phenotypes, including benign lymphoproliferation and IgG subclass deficiencies.